2022
DOI: 10.4102/sajcd.v69i2.907
|View full text |Cite
|
Sign up to set email alerts
|

Is a hybrid of online and face-to-face services feasible for audiological rehabilitation post COVID-19? Findings from three public health patients

Abstract: Background:The global coronavirus disease 2019 (COVID-19) pandemic has pushed many audiologists to incorporate remote service delivery methods to adhere to mandatory health and safety protocols. The use of tele-audiology for audiological rehabilitation may provide a sustainable, cost-effective modality to suit the existing need, particularly in low-resourced countries.Objectives: This study aimed to investigate the feasibility of implementing a hybrid tele-rehabilitation programme in a South African public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…These authors believed that although ERTL training was valuable, it was lacking in practical application and was more knowledge focused with poor theoretical coherence. These challenges with ERTL for educators had a substantial impact on their workload, which became exceptionally increased (Hlayisi, 2022 ; Khatib & Hlayisi, 2022 ; Naidoo et al, 2022 ). Naidoo et al ( 2022 ) found that educators experienced substantial challenges in coping with the extra demands brought on by the ERTL student-centred approach that COVID-19 was demanding.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors believed that although ERTL training was valuable, it was lacking in practical application and was more knowledge focused with poor theoretical coherence. These challenges with ERTL for educators had a substantial impact on their workload, which became exceptionally increased (Hlayisi, 2022 ; Khatib & Hlayisi, 2022 ; Naidoo et al, 2022 ). Naidoo et al ( 2022 ) found that educators experienced substantial challenges in coping with the extra demands brought on by the ERTL student-centred approach that COVID-19 was demanding.…”
Section: Resultsmentioning
confidence: 99%
“…• Not applicable 12. Khatib and Hlayisi (2022) Rehabilitation in the time of COVID-19: Is a hybrid telehealth approach the new norm?…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations